Self-powered piezoelectric-biosensing textiles for the physiological monitoring and time-motion analysis of individual sports - Mao, Y.; Shen, M.; Liu, B.; Xing, L.; Chen, S.; Xue, X. (Sensors, 2019)
Self-powered piezoelectric-biosensing textiles for the physiological monitoring and time-motion analysis of individual sports have been developed. The material system is composed of tetrapod-shaped ZnO nanowires on common textiles. The mechanism is based on the coupling of enzymatic reaction (LOx and lactate) and piezoelectric effect. After conformably attaching the device to the athlete, the device can monitor in real-time the moving speed, frequency, joint angle, and sweat lactate concentration of the athlete. The whole monitoring/analysis process is battery-free. The motor skills and physiological state of two athletes are investigated using the textiles, and different lactate threshold times and maximum lactate release capacities have been obtained. This technique can help them develop distinct training programs. This research is a new direction for the scientific monitoring of kinematics and may also stimulate the development of self-powered wearable sports-related systems.